1991
DOI: 10.1177/172460089100600104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative CA 15-3 Levels in Operable Breast Cancer. Comparison with Tissue Polypeptide Antigen (TPA) and Carcinoembryonic Antigen (CEA)

Abstract: CA 15-3, TPA and CEA were assayed before surgery in 60 patients with breast cancer. A significant association was found between preoperative CA 15-3 levels and some of the most important prognostic factors in breast cancer, such as lymph node status and tumor size. No similar association was discovered for CEA and TPA. Preoperative CA 15-3 levels were also significantly associated with early recurrences of the disease, thus adding useful information to prognosis especially in N+ patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Our results therefore confirm previously reported results [7][8][9][10][11][12][13][14][15][16] concerning the prognostic value of initial CA 15-3 concentration in patients without metastases at diagnosis. Cox model identified initial CA 15-3 concentration as an independent prognostic factor, the most important after lymph node invasion.…”
supporting
confidence: 83%
“…Our results therefore confirm previously reported results [7][8][9][10][11][12][13][14][15][16] concerning the prognostic value of initial CA 15-3 concentration in patients without metastases at diagnosis. Cox model identified initial CA 15-3 concentration as an independent prognostic factor, the most important after lymph node invasion.…”
supporting
confidence: 83%
“…Our study showed that patients presenting CA15-3 levels over 40U/ml (cut-off) have both worse disease free interval (DFS) and overall survival (OS) compared to those with concentrations <40U/ml. This is supported by Iaffaioli and co-workers that reported that patients with high preoperative levels of CA 15-3 (>30 U/ml) have shorter disease-free interval than patients with lower levels [28]. The present study also demonstrated that preoperative CA 15-3 levels are significantly associated with early recurrences of the disease, thus adding useful information to prognosis especially in lymph node-positive patients.…”
Section: Discussionsupporting
confidence: 87%
“…In particular, these authors reported that the median value of CA 15-3 (43kU/l) in 26 patients with stage IV disease (86% patients with bone metastasis) was significantly higher than the median for 97 patients classified as stage I or II (17 kU/I) [28]. Our study showed that patients presenting CA15-3 levels over 40U/ml (cut-off) have both worse disease free interval (DFS) and overall survival (OS) compared to those with concentrations <40U/ml.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…At least 10 published studies involving Ͼ4000 patients have addressed the relationship between preoperative concentrations of CA 15-3 and patient outcome (Table 3) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Although a range of cutoff points were used (25-40 kilounits/L), all of the identified studies apart from one concluded that high concentrations of the marker at initial presentation predicted adverse patient outcome.…”
Section: Determining Prognosismentioning
confidence: 99%